Introduction to dramatherapy : person and threshold - Pitruzzella, Salvo (Brunner-Routledge, 2004)
Beginning with a history of dramatherapy, Salvo Pitruzzella goes on to examine the issues of identity, and the mediation between the internal and external worlds.